SAMALONA ISLAND DEVELOPMENT STRATEGY IN INCREASING TOURIST VISIT IN MAKASSAR CITY - Arifin, Muh.; Sabran, Sabran; Jasman, Jasman (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Samalona Island is an island located in the Makassar Strait which is one of the Spermonde archipelago in Makassar City. The Samalona Island Development Strategy involves tourism stakeholders and looks at the 4A aspects. This study aims to determine the aspects of attractions, accessibilities, amenities and ancillary), the role of stakeholders in the development of Samalona Island, and use SWOT analysis. The results of this study indicate that Samalona Island is an island that has marine potential that can be developed. The development of Samalona Island involves tourism stakeholders consisting of the government through the Makassar City Disparekraf, tourism business actors, and the local community of Samalona Island. The role of stakeholders in the development of Samalona Island is in the form of providing infrastructure, fostering human resources, empowering local communities, and promoting. A SWOT analysis was carried out to find out the opportunities and threats and to find out the strengths, weaknesses, opportunities and threats of the island of Samalona.